تحليل الكثافة الاحتمالية لمتوسطات درجات الحرارة السنوية الحدية في بعض محطات المنطقة الساحلية السورية باستخدام منحنى التوزيع الطبيعي - قره فلاح رياض (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يهدف هذا البحث إلى تحليل ميل خط الاتجاه العام لمتوسط درجات الحرارة السنوية الجافة في بعض محطات الساحل السوري خلال الفترة 1970-2010 لتحديد مقدار تغير درجة الحرارة وتأثير هذا التغير على تغير الكثافة الاحتمالية لحدوث متوسطات درجات حرارة سنوية متطرفة أو شاذة. أشارت النتائج إلى وجود ارتفاع في درجة الحرارة في جميع المحطات بين 0.8 و2 درجة سلسيوس وكان هذا الارتفاع هام إحصائيا، كما لم تنخفض درجة الحرارة في جميع المحطات عن معدلها العام خلال العقد الأول من القرن 21 مما ساهم في ارتفاع المتوسط السنوي لدرجة الحرارة الجافة خلال الفترة 2001-2010 بالمقارنة مع الفترة 1970-2000. دل تحليل الكثافة الاحتمالية لدرجة الحرارة باستخدام منحنى التوزيع الطبيعي في الفترة 2001-2010 إلى وجود تزايد كبير في احتمال ارتفاع متوسط درجات الحرارة السنوية إلى قيم حدية عليا كان احتمال الوصول إليها في الثلاثة عقود الأخيرة لا يتجاوز 5%، أما القيم الحدية الدنيا لمتوسط درجة الحرارة فقد انعدم احتمال حدوثها وأصبحت أعلى بكثير عما كانت عليه في العقود الثلاثة الأخيرة من القرن الماضي. This piece of research analyzes the general-index change of annual medium temperatures in some stations of the Syrian Coast during the years 1970-2010, so as to identify the amount of change in temperatures and the effect of such a change on the probable density that results in annual medium temperatures that are both extreme and unnormal. Results point to an increase in temperatures in all those stations between 0.8 and 2 Celsius degrees. This increase is significant statistically. At the same time, temperatures had not gone lower than their general average in all those stations during the first decade of the 21st century, contributing to an increase of the annual average of temperature during the years 2001-2010 in comparison with the years 1970-2000. Using Natural Distribution Diagram during the years 2001-2010, analysis of the probable density of temperature refers to a great increase in the possibility of having higher extreme temperatures whose value did not exceed 5% over the last three decades. By contrast, lower extreme records had zero probability and got higher than they had been during the three decades of the late century.